Sosialisasi Perizinan Pangan Industri Rumah Tangga Pada Usaha Rengginang Mentari Di Desa Kapongan - Abdullah Muhlis; Sasmita Sari; Muhammad Misbahul Hasan; Siti Miftahul Jannah; Adisty Widia Utami (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2023)
The Indonesian government implements and develops several standards and certifications which must be completed by business actors as an effort to improve the quality and competitiveness of MSME products. One of them is the Home Industry Food Production Certificate (SPP-IRT). Kapongan village is one of the well-known rengginang producing areas. However, many rengginang products produced by IRT do not yet have a PIRT permit. This PKM activity aims to increase knowledge and understanding of Rengginang Mentari business actors about the importance of PIRT for a food product. There are four stages in this community service method: preparation, implementation, evaluation and follow-up plans. The socialization was carried out on June 10 2023 with the following materials: 1) Definition of IRT, SPP-IRT and No PIRT, 2) Procedure for submitting SPP-IRT to the Situbondo District Health Office, 3) Procedures for Inspecting Household Industry Food Production Facilities, and 4) Benefits of having SPP-IRT.